2011
DOI: 10.1097/hjh.0b013e32833f5e68
|View full text |Cite
|
Sign up to set email alerts
|

Age-related and blood pressure-independent reduction in aortic stiffness after kidney transplantation

Abstract: This study shows for the first time that there is an age-dependent improvement in aortic stiffness after KTx. These observations suggest that older patients may have an added cardiovascular risk reduction after a successful KTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 34 publications
3
34
1
3
Order By: Relevance
“…Our study was different in that it followed incident patients from time of transplant, with measurements at baseline and one year, adding further information about what happens to PWV over time. Our results indicate that changes in aortic stiffness may be slowed with successful transplantation, consistent with two previous smaller studies over a shorter time period of 3 months [20, 21]. In the study by Ignace, et al aortic stiffness changes post transplantation were dependent on age, with improvement seen only in transplant recipients older than 50 years [21].…”
Section: Discussionsupporting
confidence: 90%
“…Our study was different in that it followed incident patients from time of transplant, with measurements at baseline and one year, adding further information about what happens to PWV over time. Our results indicate that changes in aortic stiffness may be slowed with successful transplantation, consistent with two previous smaller studies over a shorter time period of 3 months [20, 21]. In the study by Ignace, et al aortic stiffness changes post transplantation were dependent on age, with improvement seen only in transplant recipients older than 50 years [21].…”
Section: Discussionsupporting
confidence: 90%
“…BP was recorded six times, with a 2 min interval between each measurement, and the average of the last five measurements was used to determine the brachial systolic and diastolic BP (DBP) [26]. We determined carotid-femoral pulse wave velocity (cf-PWV) using Complior ® SP (Artech Medical, PantinFrance) as described previously [27,28]. Briefly, the sensors were positioned over carotid and femoral arteries and the transit times were measured.…”
Section: Arterial Parametersmentioning
confidence: 99%
“…Furthermore, a study of stage 5 CKD patients showed improvement in arterial compliance by reduction in PWV and AIx, at 3 months after kidney transplant [34], suggesting a possible cause-effect relationship between impaired renal function and arterial stiffness. While the reductions in AIx were comparable, patients older than 50 years of age appeared to have more pronounced reduction in PWV than the younger patients.…”
Section: Central Arterial Compliance Measurements and Outcomes In Ckdmentioning
confidence: 97%